Characteristics of the Academic Tasks that Favor Self-regulated Learning and Distributed Cognition in University Students - María Virginia Garello; María Cristina Rinaudo (Universitat Politècnica de València, 2012)
Self‐regulated learning mainly implies the monitoring and regulation of the own performance for the attainment of personal and educational goals. As a consequence, the student constructs significant learning and usually obtains good academic performance. Self‐regulated learning implies a social aspect that includes interactions with peers and teachers who act as co‐regulators of learning. The teachers would be the persons in charge of constructing social support inside the classroom, for example creating   opportunities for peer collaboration in the accomplishment of the tasks. The notion of distributed cognition allows us to express that we do not think or learn alone, but by collaborating with other people and using cultural tools. We proposed to study self‐regulated learning processes and distributed cognition in university students by means of the implementation of two studies of design where 172 students from the Universidad Nacional de Río Cuarto participated in 2007 and 2008. Across the activities and implemented protocols we could analyze the aspects of tasks that favor the students' processes of self‐regulation of their performances and their participation in collaborative processes with their partners. Such aspects would be: demands for reflection on problems that they can find in their professional role, tasks that imply some level of control and evaluation, collaborative work, instances of integration of previous knowledge, out‐of‐school tasks, instances of feedback on the tasks, tasks of metacognitive and motivational reports and tasks with possibilities of review.